Bone marrow suppression or active proliferation? An analysis of neutropenia after pegylated interferon treatment of patients with chronic hepatitis C. (December 2013) - Liu, Ya-Li; Du, Xiao-Fei; Chen, Xin-Yue; Ma, Li-Na; Guo, Dan-Dan; Lu, Jun-Feng; Cao, Zhen-Huan; Zhang, Yong-Hong
Abstract Background: Neutropenia is a common adverse effect of the treatment of chronic hepatitis C with pegylated interferon and ribavirin. However, the mechanism involved is unknown. The present study aimed to investigate the cause of treatment-induced neutropenia by determining cytokine levels in plasma and in bone marrow smears. Methods: Fifteen patients with chronic hepatitis C were enrolled in this study. Plasma cytokine levels were determined using the Luminex assay before and during treatment. We simultaneously determined the levels of granulocyte colony-stimulating factor (G-CSF), granulocyte-macrophage colony-stimulating factor (GM-CSF), and 7 other cytokines, and performed bone marrow cytology when blood cell counts indicated neutropenia. Results: Only 1 bone marrow smear indicated a low cell proliferation level, whereas active proliferation was observed in the remaining 14 patients. The levels of G-CSF, GM-CSF, interleukin (IL)-2, IL-4, IL-6, and interferon (IFN)-γ decreased significantly in patients with neutropenia (p < 0.05). In contrast, the levels of IL-8, IL-10, and tumor necrosis factor (TNF)-α showed no significant change (p = 0.713, 0.930, 0.833, respectively) before or after treatment. Conclusions: The bone marrow of most patients with IFN-induced neutropenia showed active cell proliferation. Elevated G-CSF and GM-CSF but not bone marrow suppression was observed along with neutropenia after pegylated interferon treatment, suggesting a causative role of G-CSF and GM-CSF in neutropenia.